Penerapan Sanksi Pidana Terhadap Pelaku Pemalsuan Identitas Perkawinan Dalam Pembuatan Buku Nikah - Diana, Fitri (RESAM Jurnal Hukum, 2024)
Nowadays, there are many criminal acts of counterfeiting in various forms which point to the growing modus operandi of the perpetrators of crime. One of them is the act of falsifying the Marriage Book. The purpose of this study is to determine the application of criminal sanctions against perpetrators of identity falsification in the manufacture of marriage books and to determine the efforts of the Kebayakan Religious Affairs Office in overcoming falsification of marital identity in the manufacture of marriage books. This type of research is an empirical juridical research. The data sources used are primary data and secondary data obtained from primary legal materials, secondary legal materials and tertiary legal materials. The method of collecting data is through interviews and document studies. Data analysis techniques will be analyzed qualitatively. The results of the study explain that the application of criminal sanctions against perpetrators of falsification of marriage identities on marriage books is not resolved through criminal law, only resolved through the Sharia Court by requesting the cancellation of marriages by the Office of Religious Affairs (KUA). The efforts of the religious affairs office are mostly against the crime of falsifying marital identity, namely: First, socialization efforts and second, repressive efforts (actions) against perpetrators of the crime of falsifying marital identity.